Growth of cocoa seedlings affected by application of zeolite-cocopeat-manure mixture as soil conditioner enriched by Trichoderma sp. - Zakariyya, Fakhrusy; Puspitasari, Niken; Nur’aini, Febrilia (Indonesian Coffee and Cocoa Research Institute, 2024)
The objective of this research was to study the effect of soil conditioner in different dosage levels enriched by Trichoderma sp. on cocoa seedling growth and biomass. This research was conducted in glass house Kaliwining,Experimental Station of Indonesian Coffee and Cocoa Research Institute (ICCRI), Jember, East Java, with rainfall type of D (Schmidt & Ferguson) with relatively flat topography at altitude 45 m above sea level. Complete Randomized Design using four treatments, i. e. no application of soil conditioner (control), the application of 200 grams, 400 grams, and 600 grams/polybags of soil conditioner, with 5 replications and 5 subsamples was engaged for this research. Trichoderma sp. as endophytic fungus has been detected highest in the soil conditioner that enriched with Trichoderma sp. The result of the research was the application of soil conditioner alone or combined with Trichoderma sp. could increase plant growth and plant biomass. This research finding was the addition of Trichoderma sp. with soil conditioner increased the plant growth doubled than soil conditioner alone.